Identifying farm-type specific entry points for innovations in weed management in smallholder inland-valley rice-based systems in West Africa - Touré, A.; Huat, J.; Rodenburg, J. (Informa UK Limited, 2021)
In West Africa, weeds are major production constraints in rain-fed lowland rice systems—often located in the inland valleys. Weed management technologies have been developed and promoted in such rice systems, but adoption by farmers lags behind, probably because of insufficient considerations of the system diversity or the farm-specific characteristics during technology development or promotion. This study aimed to identify farm-type specific entry points for innovations in weed management practices of smallholders in rice-based systems in inland valleys. We conducted farm surveys in the Mono Couffo region of Benin in 66 fields in 2010 and 2011 in a range of socio-economic settings typical for smallholder farms. A combination of multivariate analyses using Principal Component Analysis and Agglomerative Hierarchical Cluster is helpful in constructing farm typologies. This categorization, in turn, enables the assessment of farm-type specific weed management strategies and consequently the identification of entry points for innovation. Specific entry points for innovations in weed management include: (i) complementing the existing range of curative options by more preventive measures, (ii) diversifying the existing range of curative measures (mainly hand weeding and herbicide application) by measures that are both non-chemical and labor-saving, and (iii) improving women farmers’ access to information and inputs by targeted training endeavors and conducive credit systems.